Identification and In Vitro Functional Verification of Two Novel Mutations of GHR Gene in the Chinese Children with Laron Syndrome - Li, Ran; Gong, Fengying; Pan, Hui; Liang, Hanting; Miao, Hui; Zhao, Yuxing; Duan, Lian; Yang, Hongbo; Wang, Linjie; Chen, Shi; Zhu, Huijuan (Frontiers in Endocrinology, 2021)
Purpose: Laron syndrome (LS) is a severe growth disorder caused by GHR gene mutation or post-receptor pathways defect. The clinical features of these patients collected in our present study were summarized, GHR gene variants were investigated and further in vitro functional verification was carried out. Methods: Four patients with LS were collected, their clinical characteristics were summarized, genomic DNA was extracted, and GHR gene was amplified and sequenced. GHR wild type (GHR-WT) and mutant GHR expression plasmids were constructed, and transiently transfected into HepG2 cells and HEK293T cells to observe the subcellular distribution of the GHR protein by immunofluorescence and to determine the expression of GHR and its post-receptor signaling pathway changes by Western blotting. Results: All of the four patients were male, and the median height was -4.72 SDS. Four GHR gene variants including c.587A>C (Y196S), c.766C>T (Q256X), c.808A>G (I270V) and c.1707-1710del (E570fs) were identified, and the latter two were novel mutations. The results of mutant GHR plasmids transfection experiments and immunofluorescence assay showed that the subcellular distribution of GHR-Q256X and GHR-E570fs mutant proteins in HepG2 and HEK293T cells presented with a unique ring-like pattern, gathering around the nucleus, while GHR-Y196S mutant protein was evenly distributed on HepG2 cell membrane similar to GHR-WT. The GHR protein levels of HepG2 cells transiently transfected with GHR-Y196S, GHR-Q256X and GHR-E570fs were all significantly lower when compared with cells transfected with GHR-WT (P<0.05). Further mutant GHR post-receptor signal transduction investigation demonstrated that GH induced phosphorylated STAT5 levels of HepG2 cells transfected with three mutant plasmids were all significantly decreased in comparison with that of GHR-WT (P<0.05) . Conclusions: Two novel GHR gene mutations (I270V and E570fs) were found in our patients with LS. GHR mutations influenced the subcellular distribution and GHR protein levels, then led to the impaired post-receptor signal transduction, suggesting that the GHR mutations contributed to the pathological condition of LS patients.